Polymers from Fossil and Renewable Resources Scientific and Technological Comparison of Plastic Properties - Ciardelli, Francesco; Bertoldo, Monica; Bronco, Simona; Passaglia, Elisa (Springer International Publishing : Imprint: Springer, 2019)
The book describes the development and commercialization of materials with viscoelastic properties, placing particular emphasis on the scientific and technological differences between plastics and bioplastics. The authors explain how to handle each of the two types of materials and determine the comparative environmental impact of the material life-cycle. The practical values of the overlapping aspects of the two types of materials from technical properties to eco-compatibility are also discussed.